PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PUBLIK DALAM PEMBUATAN SURAT IZIN MENGEMUDI (SIM) DI KEPOLISIAN RESORT KUTAI BARAT TAHUN 2016 - HANDAYANI PUTRI, ISABELLA AMELIA (EKONOMIA, 2017)
The population in this study is the West Kutai people who took care of making a driver's license (SIM) at the Police Resort Kutai Barat using slovin formula, the importance of the sample in this study were 94 respondents. Mechanical Sampling in this study conducted by accidental sampling technique. Methods of data collection using questionnaires and documentation. The analysis technique used is multiple regression.Â Results of analysis using SPSS version 14 indicates that: Fifth variable reliability, responsiveness, assurance, empathy, tangible simultaneously significant effect on people's satisfaction test results Fhitung 7.552 with a significance level of 0.000, using a significance value of 0.000 for significance value <0, 05. Tangible (physical form) the dominant influence on satisfaction of the people in the manufacture of SIM (Manes's license) in Kutai Barat district police. Reliability (reliability) significant negative effect on people's satisfaction in the manufacture of SIM (Manes's license) in Kutai Barat district police